Violence Against Doctors - Khan, Mohammad Ashik Imran; Ahasan, HAM Nazmul; Mahbub, Md Shahriar; Alam, Md Billal; Miah, Md Titu; Gupta, Ratan Das (Journal of Medicine, 2010)
DOI: 10.3329/jom.v11i2.5465 J MEDICINE 2010; 11 : 167-169